2021
DOI: 10.4236/ojneph.2021.111010
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone as a Marker for the Red Cell Fragility in Different Stages of Chronic Kidney Disease

Abstract: Objective: The aim of the work is to study the relationship between Red blood cell osmotic fragility and level of parathyroid hormone in patients with different stages of Chronic Kidney Disease including End Stage Renal Disease. Background: Anaemia is one of the common complications associated with Chronic Kidney Disease (CKD) responsible for the increase in the morbidity and mortality in such patients. Several factors have been attributed to causing renal anaemia, amongst which hyperparathyroidism is one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Additionally, the CKD group showed statistically lower levels of hemoglobin and platelets, and higher levels of TLC, with no significant difference in RBS levels between the groups. Anemia in CKD patients is known to be multifactorial, with its prevalence increasing from 26% to 75% as renal function declines from > 60 ml/min to < 15 ml/min, primarily due to erythropoietin (EPO) deficiency [15] . Lee et al [13] observed a bimodal distribution of low hemoglobin levels in CKD patients at ages 0-2 years (11.14 ± 1.64 g/dL) and 6-12 years (11.65 ± 1.79 g/dL).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the CKD group showed statistically lower levels of hemoglobin and platelets, and higher levels of TLC, with no significant difference in RBS levels between the groups. Anemia in CKD patients is known to be multifactorial, with its prevalence increasing from 26% to 75% as renal function declines from > 60 ml/min to < 15 ml/min, primarily due to erythropoietin (EPO) deficiency [15] . Lee et al [13] observed a bimodal distribution of low hemoglobin levels in CKD patients at ages 0-2 years (11.14 ± 1.64 g/dL) and 6-12 years (11.65 ± 1.79 g/dL).…”
Section: Discussionmentioning
confidence: 99%
“…The direct inhibitory effect of PTH on erythropoietin synthesis has been confirmed by many authors when plasma concentration of erythropoietin increased significantly after parathyroidectomy reaching to 10-folds higher than its preoperative concentration within 2 weeks or even less; the molecular pathophysiology of this inhibitory effect is not yet known [48,49]. Shortened lifespan of red blood cells has been observed in patients with CKD as a cause of anemia and it was linked to the high plasma PTH due to its role in increasing median osmotic fragility of red blood cells with consequent anemia [50]. Cinacalcet hydrochloride, a calcimimetic drug, which is used as a medical treatment of secondary hyperparathyroidism has been associated with improvement in hemoglobin level and necessitating fewer doses of erythropoiesis-stimulating agents to correct anemia [51,52].…”
Section: Pth and Anemiamentioning
confidence: 91%